Respostas
respondido por:
1
Resolução:
f(x) =![\frac{1}{ \sqrt{2+2x^2} } \frac{1}{ \sqrt{2+2x^2} }](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7B+%5Csqrt%7B2%2B2x%5E2%7D+%7D+)
f`(x) = - (0+2.2x)/(2√(2+2x^2))/√(2+2x^2)^2
f`(x) = - 4x/(2√(2+2x^2)^3)
bons estudos:
f(x) =
f`(x) = - (0+2.2x)/(2√(2+2x^2))/√(2+2x^2)^2
f`(x) = - 4x/(2√(2+2x^2)^3)
bons estudos:
respondido por:
0
F(x) 1/√2 +2x²
F'(x) = [1' *√2 +2x² - 1 * (√2 +2x²)']/(√2 +2x² )²
F'(x) = { 0 * √2 +2x² - 4x * [1/2*√2 +2x²]} / (2 +2x²)
F'(x) = { - 2x / (2 +2x²)^3/2}
*-*-*-*-*-*-*-*-*-*-*-*
16/10/2016
Sepauto
SSRC
*-*-*-*-*-*-*-*-*-*-*-*
F'(x) = [1' *√2 +2x² - 1 * (√2 +2x²)']/(√2 +2x² )²
F'(x) = { 0 * √2 +2x² - 4x * [1/2*√2 +2x²]} / (2 +2x²)
F'(x) = { - 2x / (2 +2x²)^3/2}
*-*-*-*-*-*-*-*-*-*-*-*
16/10/2016
Sepauto
SSRC
*-*-*-*-*-*-*-*-*-*-*-*
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás